Influence of citric acid and oleic acid coating on the dc magnetic properties of Fe3O4 magnetic nanoparticles. (2020) - Polichetti, M.; Modestino, M.; Galluzzi, A.; Pace, S.; Iuliano, M.; Ciambelli, P.; Sarno, M.
Abstract: The properties of two samples of Fe3 O4 magnetic nanoparticles coated with citric acid and oleic acid respectively, have been studied by means of DC magnetic measurements. The analysis has been performed by measuring the Zero Field Cooling (ZFC) and Field Cooling (FC) magnetization curves as a function of the temperature, at 0.01 T applied field. In this framework, the blocking temperature (TB ) distribution and the effect of the coatings on the experimentally evaluated samples properties have been analysed. Moreover, the magnetization as a function of the field has been measured at temperatures above TB and the comparison between the results obtained for the two samples has been discussed.